The Horse soldiers - Ford, John, 1894-1973.; Mahin, John Lee, 1907-; Rackin, Martin; Wayne, John, 1907-1979.; Holden, William, 1918-1981.; Towers, Constance; Buttolph, David, 1902-1983.; Sinclair, Harold, 1907-1966.; Mirisch Company ([Culver City, CA] : MGM/UA Home Video, 1990)
It is 1863, the rough and rugged Colonel Marlowe is in command of a motley assortment of 1200 Union volunteers. Their task is to infiltrate 300 miles of Southern territory and destroy the most strategic rail route in the Confederacy.
Closed-captioned for the hearing impaired.
Based on the novel by Harold Sinclair.
Originally produced as motion picture in 1959.
MGM/UA Home Video: M201772.
Director of photography, William Clothier ; film editor, Jack Murray ; music, David Buttolph.
John Wayne, William Holden, Constance Towers.
Keywords: War films; Feature films; United States -- History -- Civil War, 1861-1865 -- Drama